Electric power generation from a turnstile (2020)
This research aimed to design, simulate in SolidWorks, build, and test two energy conversion mechanisms using mechanical gears and through 0 neodymium magnets. The used source of mechanical energy was the rotational movement of the turnstile arm, generated by pedestrians who enter and leave the campus at Escuela Colombiana de Ingeniería Julio Garavito. To achieve it, the following tasks were performed: the literature review, parameterization of pedestrians’ entrance and exit, characterization of the turnstile, simulation, construction, and the assessment of the mechanisms. The obtained energy conversion results varied from 7v to 11v (1W) for the mechanism using neodymium magnets, and from 12v to 17v (12W) for the mechanical gears. The developed system aims to promote environmental commitment and exploit the lost energy resulting from people’s daily activities.